Colord Image White Cracks In-Painting Method - Mohammed , Faisel G.; Khanjar, Rajaa J. (Iraqi Journal of Science, 2022)
The gaps and cracks in an image result from different reasons and affect the images. There are various methods concerning gaps replenishment along with serious efforts and proposed methodologies to eliminate cracks in diverse tendencies. In the current research work a color image white crack in-painting system has been introduced. The proposed inpainting system involved on two algorithms. They are Linear Gaps Filling (LGF) and the Circular Gaps Filling (CGF). The quality of output image depends on several effects such as: pixels tone, the number of pixels in the cracked area and neighborhood of cracked area and the resolution the image. The quality of the output images of two methods (linear method: average Peak Signal to Noise Ratio (PSNR)=24.899 and circular method: average PSNR= 27.783). The result of correlation of images is close to the original image (horizontal = 0.894, vertical = 0.521, and diagonal =0.807). The first method is less time consuming than the circular method.